THE RESULTS OF USE INTERSPECIFIC HYBRIDS WITH PARTICIPATION OF SPECIES SOLANUM BULBOCASTANUM DUN. IN POTATO BREEDING - A. Ad. Podgaietskiy (Труды по прикладной ботанике, генетике и селекции, 2018)
There has idendified a capacity of interspecific hybrids involving wild species Solanum bulbocastanum Dun. to create new potato varieties. A possibilities of using the breeding material for the valuable commercial traits, including adaptation to environmental conditions, resistance to pests and diseases. The genealogy of created varieties, including the origin of the secondary interspecific hybrids and backcrosses has demonstraded.